Propuesta de un plan de control de fatiga para los trabajadores de la empresa Minera Arirahua S.A. Condesuyos, Arequipa 2015 - Paiva Flores, Juan Carlos (2017)
The present thesis entitled: "PROPOSAL OF A FATIGUE CONTROL PLAN FOR THE CONDUCTORS OF THE CONCENTRATED OPERATION OF THE TRANSPORTATION COMPANY" SERVOSA CARGO SAC, AREQUIPA, 2017 "has as general objective the control of fatigue to reduce accident rates In the transport company. The present research is of great interest since within the field of interest of the ergonomics is the study and prevention of fatigue, especially in the tasks of the conductors of the companies. The type of research used is descriptive research with univariate descriptive non-experimental design. For the collection of the information, a survey was applied to all personnel in the area of operations of concentrate. After having applied the survey will proceed to the design of the proposal of control of fatigue to improve the working conditions of the drivers.